2015
DOI: 10.4038/tar.v24i1.7988
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Three Commercially Grown Banana (<i>Musa acuminata </i>Colla) Cultivars in Sri Lanka

Abstract: Physical and mechanical properties of banana (Musa acuminata Colla) are necessary to design handling and packaging equipment, and for safe transportation. The postharvest losses of banana in Sri Lanka are about 30 % and the mechanical damage during transport and handling contributes largely for these losses. Further, about 97 % of fruits are handled by the traditional marketing channels under poor postharvest handling practices and therefore, safe handling and transport is of prime importance at present. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
1
10
1
Order By: Relevance
“…The Shail variety contained the highest amount of moisture (76.23%) whereas the Bichi variety contained less moisture (73.49%). The approximate moisture content of Embul, Seeni and Kolikuttu varieties of banana at the harvest maturity were 77.86%, 72.46% and 75.97% respectively, according to Wasala, Dharmasena, Dissanayake, and Thilakarathne (2012) which supports the present study. Similar values were reported by Kachru, Kotwaliwale, and Balasubramanian (1995) for some Indian banana varieties at maturity.…”
Section: Physicochemical Propertiessupporting
confidence: 89%
“…The Shail variety contained the highest amount of moisture (76.23%) whereas the Bichi variety contained less moisture (73.49%). The approximate moisture content of Embul, Seeni and Kolikuttu varieties of banana at the harvest maturity were 77.86%, 72.46% and 75.97% respectively, according to Wasala, Dharmasena, Dissanayake, and Thilakarathne (2012) which supports the present study. Similar values were reported by Kachru, Kotwaliwale, and Balasubramanian (1995) for some Indian banana varieties at maturity.…”
Section: Physicochemical Propertiessupporting
confidence: 89%
“…Reference [18] characterizing agronomically, physically and chemically banana fruits reported similar length and diameter values in 26 banana accessions of the active genebank of Embrapa. Average fruit lengths of Embul, Seeni and Kolikuttu cultivars are 10.5 ± 0.86, 10.5 ± 0.86 and 14.3 ± 1.66 cm, respectively according to Reference [29] report. The length values reported were significantly lower than those observed in the current work.…”
Section: Size Weight and Firmness Attributes Of Keitt Mangoes And Camentioning
confidence: 93%
“…Reference [28] reported similar centesimal mango composition as obtained in the current work. Reference [29] reported that the average centesimal composition of Embul, Seeni and Kolikuttu cultivars of banana at the harvest maturity indicated that the moisture, protein and fiber contents of three banana cultivars are not significantly different (p < 0.05). Therefore, Mozambique mango and banana fruits present high moisture than reported in some literatures depending on local fruit production and the moisture increases from green to the ripe fruits for all regions.…”
Section: Fruit Centesimal Compositionmentioning
confidence: 99%
“…1). Styrofoam sheets were identified as the cushioning material to be used for banana bunches in bulk transportation after evaluating its protective qualities on banana (Wasala et al, 2012). Styrofoam, a commonly used cushioning material for fruits, has a high mechanical strength in compression, tension, bending and shear, and has smooth surface, high water and vapour resistance properties.…”
Section: Methodsmentioning
confidence: 99%